KEDUDUKAN DAN HAK ANAK LUAR NIKAH PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 TENTANG STATUS ANAK LUAR NIKAH - Nurul Hak (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2018)
This article describes that since the ruling of the Constitutional Court No. 46/ PUU-VIII / 2010 concerning the status of children out of wedlock, there are pros and cons in the community in responding to the decision. Because this decision is on the one hand different from the provisions in Law No. 1 of 1974 and contrary to the fatwa of the Indonesian Ulama Council No. 11 of 2010 concerning the position of adultery children and treatment of them, on the other hand in their implementation requires implementation regulations which up to now do not yet exist. In the decision of the Constitutional Court it became clear the legal position of zina children or children born without going through the door of marriage, as illegitimate children, he only had a civil relationship with his mother and his mother's family. For men who cause their birth to be subject to ta'zir punishment, by providing a living and living necessity, the punishment is solely to provide protection for the child, so that the child gets the proper life insurance. The civil relationship of the child of adultery results does not cause a nasab relationship, but requires the biological parents to provide a guarantee of life for their child. If an adultery child is a woman, if she wants to get married, then the right to become a guardian is the guardian of the judge, while her parents, in this case her biological father is obliged to hold the marriage ceremony.